2016
DOI: 10.1097/ta.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography abbreviated assessment of sarcopenia following trauma

Abstract: Background Older adult trauma patients are at increased risk of poor outcome, both immediately after injury and beyond hospital discharge. Identifying patients early in the hospital stay who are at increased risk of death after discharge can be challenging. Methods Retrospective analysis was performed using our trauma registry linked with the social security death index from 2010–2014. Age was categorized by 18–64 and ≥65 years. We calculated mortality rates by age category then selected elderly patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Studies like Chang et al 21 calculated SMI using lean muscle mass, obtained by setting density thresholds to exclude fatty infiltrate in the imaging software used to calculate CSA. A more holistic approach was taken by Leeper et al , normalizing psoas CSA using a calculated value for body surface area (BSA) 6. Akahoshi et al similarly used calculated BSA to generate an estimate for psoas CSA, and defined sarcopenia as a difference between estimate and actual psoas CSA 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies like Chang et al 21 calculated SMI using lean muscle mass, obtained by setting density thresholds to exclude fatty infiltrate in the imaging software used to calculate CSA. A more holistic approach was taken by Leeper et al , normalizing psoas CSA using a calculated value for body surface area (BSA) 6. Akahoshi et al similarly used calculated BSA to generate an estimate for psoas CSA, and defined sarcopenia as a difference between estimate and actual psoas CSA 22…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is characterized by loss of skeletal muscle, decreased muscle strength and low physical performance 4. It has been demonstrated that the presence of sarcopenia is a marker for poor outcome in the elderly with a critical illness5 or traumatic injury 6 7. These patients therefore may require modification and personalization of care and interventions to counteract the increased likelihood of adverse health events 8.…”
Section: Introductionmentioning
confidence: 99%
“…Also, low psoas CSA in relation to L4 vertebra size is associated with an increased risk for complications during hospital stay . Importantly, low muscularity as determined by measuring psoas CSA using abdominal CT scans recently emerged as a predictor of mortality in elderly trauma patients . On the other hand, CSA of the paraspinal muscles, determined using MRI, is reported to decrease following prolonged bed rest in healthy adults .…”
Section: Discussionmentioning
confidence: 99%
“…7 Importantly, low muscularity as determined by measuring psoas CSA using abdominal CT scans recently emerged as a predictor of mortality in elderly trauma patients. 5,6 On the other hand, CSA of the paraspinal muscles, determined using MRI, is reported to decrease following prolonged bed rest in healthy adults. 9 Although our work demonstrated that linear measures of the paraspinal muscles yielded less variability and a stronger correlation with total L3 muscle CSA compared with the psoas muscle group, the combined linear measures products of psoas and paraspinal muscles exhibited a stronger correlation and a greater ability to correctly identify patients with low skeletal muscle index values.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviated methods to screen for low muscle from routine CT imaging have been proposed in intensive care and trauma populations,24 and to a limited extent in cancer patients, where results have been mixed 25, 26. One recently proposed method27 allows the user to quickly assess patient muscularity using the combined area of the psoas and paraspinal muscles computed from linear measurements that take <2 min per patient.…”
Section: Introductionmentioning
confidence: 99%